Effectiveness of A Health Behavior Module Based on Transcultural Nursing in Efforts to Prevent Cardiovascular Complications on Hypertension Patients in the Community - Israfil, Israfil; Yusuf, Ah; Efendi, Ferry (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is a chronic non-communicable disease which, if not treated properly, will cause cardiovascular complications which are the cause of disability and death in communities throughout the world. Patient behavior that does not follow hypertension management guidelines is a major factor in the risk of cardiovascular complications in hypertensive patients in the community. The aim of this research is to determine the effectiveness of a health behavior module based on transcultural nursing in preventing cardiovascular complications and its impact on hypertensive patients in the community. The research design was a quasi experiment with a pre-post-test control group design. The sample size was 100 hypertension patients divided into 50 treatment groups and 50 control groups. The research sample was taken using a purposive sampling technique based on predetermined inclusion criteria. The research data were analyzed descriptively, homogeneity test using Levene Statistics, Wilcoxon pre-post difference test for each group, simultaneous pre-post difference test for both groups with Mann-Whitney, and correlation test with Spearman Rho. Results of the test for equality of respondent characteristics p-value = > 0.05, Wilcoxon test in the treatment group p-value = 0.000, control group p-value = > 0.05, Mann Whitney test pre test p-value > 0.05, post test < 0.05, and the Spearman rho test obtained a p-value < 0.05. Conclusion: The behavioral module intervention to prevent cardiovascular complications based on transcultural nursing has proven to be effective in increasing efforts to prevent cardiovascular complications in hypertensive patients, and efforts to prevent cardiovascular complications based on transcultural nursing have a significant relationship in reducing systolic, diastolic blood pressure and cholesterol levels in hypertensive patients in the community. It is hoped that this module can become a health promotion media that can be used to increase efforts to prevent cardiovascular complications in hypertensive patients in the community